2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder among paramedic and hospital emergency personnel in south-east Iran

Abstract: BACKGROUND: Paramedic and emergency personnel may encounter directly many events that threat their own wellbeing during their daily work. This study was conducted to examine the prevalence rate of post-traumatic stress disorder (PTSD) among two groups of paramedic and emergency personnel in southeast Iran. METHODS: The study employed a descriptive design and was conducted in four hospital emergency wards and a pre-hospital emergency base supervised by Kerman Medical University. Using Mississippi PTSD, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
3
31
1
Order By: Relevance
“…The prevalence of PTSD is higher than estimated by Berger et al (2012) for paramedics in other European countries or Koelkebeck et al study (2015) which showed a prevalence of 0.9-2.6% of PTSD in clinical practice across Europe. Bennett et al (2004) and Iranmanesh et al (2013) on the other hand found higher PTSD incidence among emergency medical technicians and paramedics (22% in UK and 94% in Iran). The estimation of the PSTD prevalence can vary according to the strictness of the criteria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence of PTSD is higher than estimated by Berger et al (2012) for paramedics in other European countries or Koelkebeck et al study (2015) which showed a prevalence of 0.9-2.6% of PTSD in clinical practice across Europe. Bennett et al (2004) and Iranmanesh et al (2013) on the other hand found higher PTSD incidence among emergency medical technicians and paramedics (22% in UK and 94% in Iran). The estimation of the PSTD prevalence can vary according to the strictness of the criteria.…”
Section: Discussionmentioning
confidence: 96%
“…The study of Rybojad et al (2016) showed an even higher percentage of the total prevalence of PTSD in the group of polish paramedics which was 40.0% (64.3% for women and 36.1% for men). Iranmanesh, Tirgari, and Bardsiri (2013) found that most paramedics (94%) and hospital emergency personnel reported moderate PTSD. The emergency personnel reported a higher score of M-PTSD than the paramedic personnel in all subscales.…”
Section: Introductionmentioning
confidence: 99%
“…It is related to disturbing thoughts, anxiety, sleep disturbance, and avoidance of a traumatic event that ultimately leads to social, occupational and interpersonal disorders (1)(2)(3). Emergency Medical Services personnel experience workplace events that are direct threats to their well-being; they are also faced with events that have severe injuries (4). The present study is a report of the result of a systematic review and metaanalysis.…”
Section: Dear Editormentioning
confidence: 96%
“…We used valid English and Persian keywords including post-traumatic stress disorder (PTSD), paramedic, Emergency Medical technicians, mental health disorder, Pre-Hospital Emergency staff, Iran, pre-Hospital Emergency personnel, and Emergency Medical Services (EMS) with operators (AND) and (OR) without time limit until April 2019. After applying the eligibility criteria and qualitative evaluation, finally, three studies with good quality were included in the meta-analysis (2,4,6). The prevalence of PTSD and sample size were extracted from each article and binomial distribution was used to calculate the variance of each study.…”
Section: Dear Editormentioning
confidence: 99%
“…5 The most important duty of the emergency system is taking immediate action to rescue patients and also emergency is one of the main medical services, and it is often in the first line of the interaction of the patients and the health care system. 6,7 Manpower has an important role in changing and improving the health care system, and it is one of the crucial parts of the organizations that have been emphasized by the experts in human resources management. 8 Ignoring motivational conditions of the nurses leads to low occupational satisfaction and motivation, low quality of the services, slow recovery process, and lack of satisfaction of the people from health care services.…”
Section: Introductionmentioning
confidence: 99%